2016
DOI: 10.1155/2016/6321906
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiographic and Microbiological Evaluation of High Level Laser Therapy, a New Photodynamic Therapy Protocol, in Peri-Implantitis Treatment; a Pilot Experience

Abstract: Aim. Endosseous implants are widely used to replace missing teeth but mucositis and peri-implantitis are the most frequent long-term complications related with dental implants. Removing all bacterial deposits on contaminated implant surface is very difficult due to implant surface morphology. The aim of this study was to evaluate the bactericidal potential of photodynamic therapy by using a new high level laser irradiation protocol associated with hydrogen peroxide in peri-implantitis. Materials and Methods. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 27 publications
1
43
0
2
Order By: Relevance
“…2016 reported the values of 810, 690 and 660 nm, respectively. The times used for activation of the photosensitizer were also reported heterogeneously, ranging from 10 to 60 s .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2016 reported the values of 810, 690 and 660 nm, respectively. The times used for activation of the photosensitizer were also reported heterogeneously, ranging from 10 to 60 s .…”
Section: Discussionmentioning
confidence: 99%
“…The singlet oxygen is an oxygen free radical that determines bacterial cell death. In many of the studies, the results showed a decrease in total bacterial count (7,8,14,16,(25)(26)(27)(28)(29). The great majority of bacteria investigated were of Gram-negative and were affected by aPDT (7,8,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, mechanical curettage has been found to be insufficient for implant surface decontamination due to the presence of bacteria in surface micro-irregularities, and new therapeutic strategies have been developed to improve treatment outcomes [7]. For instance, laser treatments, antiseptics, and antibiotics have been reported as curative alternatives [8]. To develop and evaluate potential periimplantitis treatment procedures, several in vitro studies have been and are still conducted.…”
Section: Introductionmentioning
confidence: 99%